Nutrient Uptake and Related Efficiencies in a Fodder Sorghum (Sorghum bicolor L.) – Mustard (Brassica juncea L.) Cropping Sequence as Influenced by Nitrogen, Phosphorus and Bio-inoculant inputs - Ramanjaneyulu, A. V.; Shivay, Y. S.; Giri, G.; Singh, Teekam (International Journal of Bio-resource and Stress Management, 2023)
The productivity of mustard in North West India is low especially when it is preceded by crops like fodder sorghum and is mainly due to improper or imbalanced use of nutrient inputs. An experiment involving fodder sorghum-mustard sequence was carried out during 2003-04 and 2004-05 at the Research farm of Agronomy Division, Indian Agricultural Research Institute, New Delhi, India. The objective of experiment was to study the effect of N, P and biofertilizers [Azotobacter and phosphate solubilizing bacteria (PSB)] on the productivity, nutrient dynamics and economic viability of a fodder sorghum – mustard sequential system. It was observed that the fodder yield of sorghum with recommended dose of fertilizers (RDF, 60 kg N + 12.9 kg P ha-1) and half RDF + biofertilizers on fresh as well as dry weight basis was statistically similar and superior to half RDF and control. Observations on succeeding crop of mustard showed that the seed yield was highest due to applied RDF (residual or direct) was on par with that of half RDF + biofertilizers. The mustard seed equivalent yield had similar trend as seed yield of mustard. Agronomic efficiency and apparent recovery efficiency of N in mustard and also b:c ratio of fodder sorghum-mustard sequence were highest with directly applied half RDF + biofertilizers treatment.